2019
DOI: 10.1111/all.14069
|View full text |Cite
|
Sign up to set email alerts
|

Secondary prevention measures in anaphylaxis patients: Data from the anaphylaxis registry

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. AbstractBackground: Patients with a history of anaphylaxis are at risk of future anaphylactic reactions. Thus, secondary prevention measures are recommended for these patients to prevent or attenuate the next reaction.Methods: Data … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…3 ). Children were more frequently prescribed > 1 AAI, which is consistent with data form the Anaphylaxis Registry in which ~ 50% of children were prescribed > 1 AAI compared with ~ 30% of adults [9 ]. There are significant geographical factors involved, as up to 92% children are prescribed 2 + AAIs in the UK, although this is likely to be a combination of children being prescribed one AAI for personal use and a separate AAI for school [10 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…3 ). Children were more frequently prescribed > 1 AAI, which is consistent with data form the Anaphylaxis Registry in which ~ 50% of children were prescribed > 1 AAI compared with ~ 30% of adults [9 ]. There are significant geographical factors involved, as up to 92% children are prescribed 2 + AAIs in the UK, although this is likely to be a combination of children being prescribed one AAI for personal use and a separate AAI for school [10 ].…”
Section: Discussionsupporting
confidence: 84%
“…Recent data from the EAACI revealed that only 59% of the allergists who answered a single questionnaire were following these recommendations (unpublished data). Data from the Anaphylaxis Registry show that 35% of patients with a history of anaphylaxis treated in tertiary allergy centers were prescribed more than one AAI [9]. Our data confirm the lack of consensus regarding the number of AAIs to prescribe, although following the EAACI guidelines [1], experts tended to prescribe more AAIs if the patient had mastocytosis, asthma, excess body weight, a history of severe anaphylaxis, or restricted access to immediate emergency treatment (Fig.…”
Section: Discussionsupporting
confidence: 69%
“…The European Anaphylaxis Registry, which contains data from patients with anaphylactic reactions, has been covered by several publications. 4,6,22 Serum samples from 48 patients with a history of Hymenoptera sting anaphylaxis were collected in 2010-2019. A group of 27 healthy subjects served as controls.…”
Section: Anaphylaxis Registry Data Extraction and Analysismentioning
confidence: 99%
“…According to the data from the Anaphylaxis Registry (131), an AAI prescription was offered to only 37% of the patients ouside specialized centers compared to 84% of the patients in specialized allergy centers, highlighting the need of better education for primary healthcare and emergency physicians to follow guidelines. In the multivariate analysis, the elicitor of the reaction (less prescriptions in patients with food allergy than in those with venom allergy), age of the patient (less prescriptions in babies and elderly patients), mastocytosis as comorbidity, severity of the reaction, and reimbursement/ availability of the autoinjector influence physician's decision to prescribe one (131). An integral part of the anaphylaxis action plan is represented by advising patients to carry the device with them at all times, as well as instructing the patient on how to use the autoinjector through educational material and practical training (1,2).…”
Section: Acute Treatment: Adrenalinementioning
confidence: 99%